STEM-16. TARGETING THE SCF UBIQUITIN LIGASE IN GLIOBLASTOMA - Pinkham, Kelsey (Neuro Oncol, 2017)
Glioblastoma (GBM) is the most malignant and common form of brain tumors with high mortality and resistance to therapy. The presence of glioma stem cells (GSCs) that drive tumor growth and promote recurrence exacerbates GBM prognosis. Because of its implication in cancer, and its role in regulating several proteins with oncogenic or tumor suppressor properties, we investigated the role of the SKP1–CUL1–F-Box protein (SCF) E3 ubiquitin ligase in GBM and particularly in GSCs. We demonstrate increased expression of SCF components in GBM and correlation with a worse prognosis. The downregulation of SKP1 and CUL1, two essential proteins in this complex, or blocking SKP1 binding to CUL1, resulted in GBM cell death, depletion of stem cell markers in patient-derived GSCs, and decreased tumorigenicity in mouse orthotopic GSC models. Disrupting the SCF in normal cells did not affect cell viability thereby suggesting that the role of SCF is tumor-specific and would represent an ideal therapeutic target. We show that SCF regulates c-Myc, a master regulator in GBM, implicated in tumor initiation, progression and the maintenance of self-renewal properties in GSCs. Importantly, we demonstrate that CUL1 controls the transcriptional regulation of c-Myc by increasing its promoter activity independently of the ubiquitin ligase function of this complex; CUL1 ectopic expression results in increased c-Myc transcription and protein expression, while CUL1 downregulation depleted c-Myc expression. We identified a small-molecule compound that downregulated CUL1 and consequently c-Myc and decreased GSCs proliferation in culture. This compound has been clinically used for decades and readily crosses the blood-brain-barrier. In summary, we have identified an essential role of SCF in GSCs maintenance, and a new mechanism of SCF-mediated regulation of c-Myc in GBM. We also provide a new strategy to indirectly target the “undruggable” oncoprotein c-Myc by inhibiting the expression of CUL1.